If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -63 + 12y + 3 = 5(3y + -5) + -8 Reorder the terms: -63 + 3 + 12y = 5(3y + -5) + -8 Combine like terms: -63 + 3 = -60 -60 + 12y = 5(3y + -5) + -8 Reorder the terms: -60 + 12y = 5(-5 + 3y) + -8 -60 + 12y = (-5 * 5 + 3y * 5) + -8 -60 + 12y = (-25 + 15y) + -8 Reorder the terms: -60 + 12y = -25 + -8 + 15y Combine like terms: -25 + -8 = -33 -60 + 12y = -33 + 15y Solving -60 + 12y = -33 + 15y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-15y' to each side of the equation. -60 + 12y + -15y = -33 + 15y + -15y Combine like terms: 12y + -15y = -3y -60 + -3y = -33 + 15y + -15y Combine like terms: 15y + -15y = 0 -60 + -3y = -33 + 0 -60 + -3y = -33 Add '60' to each side of the equation. -60 + 60 + -3y = -33 + 60 Combine like terms: -60 + 60 = 0 0 + -3y = -33 + 60 -3y = -33 + 60 Combine like terms: -33 + 60 = 27 -3y = 27 Divide each side by '-3'. y = -9 Simplifying y = -9
| 20d+-4=16 | | a-3.2=55 | | -75=-5(5+2n) | | 7(c-2)+6=3+c-11 | | -3+12t=-7 | | 2(x+3)-4(3x-1)+6-(5x-2)+3x=0 | | 15=3+-3n | | 106=-8k+6 | | 0.40x+0.27y= | | .8y-8=.4+16 | | 4(8m-7n)+6(3n-4m)= | | 16x-31=33 | | 6(2n-4)=-72 | | 38.6+y=54.3 | | 5(3+6x)=285 | | 0.1x-2=11 | | 0.35x+0.35y= | | 2(x+3)=2x+12-6 | | 3r^2-9r+6= | | 19+15j+1=-19+6(4j-19) | | -16h+-1=15 | | -30=5b | | 4a+16+9= | | -4(4p+2)=-72 | | 5x+5=12.5 | | .5x+7=3x-8 | | -2(p-9)=0 | | 5*x*5=125 | | 0.20y-0.20x= | | -80=4(-6n+4) | | 30-14*2+8= | | 8(-z-18)+8z=-4-14z |